Defibrillator Implantation in Patients with Nonischemic Systolic Heart Failure - Køber, Lars; Thune, Jens J; Nielsen, Jens C; Haarbo, Jens; Videbæk, Lars; Korup, Eva; Jensen, Gunnar; Hildebrandt, Per; Steffensen, Flemming H; Bruun, Niels E; Eiskjær, Hans; Brandes, Axel; et al. (The New England journal of medicine, 2016)
In a randomized trial, more than 1100 patients with nonischemic heart failure (left ventricular ejection fraction ≤35%) were assigned either to receive or not to receive an ICD. At a median of 67.6 months, there was no significant difference in mortality between the two groups. In both European and U.S. guidelines, prophylactic implantation of an implantable cardioverter–defibrillator (ICD) is a class 1 recommendation for patients with heart failure and reduced left ventricular systolic function. 1 , 2 However, the evidence for a benefit is much stronger for patients with ischemic heart disease than it is for patients with heart failure from other causes. Over the past two decades, ICD implantation has been shown to be associated with substantial reductions in the rate of sudden cardiac death and total mortality in patients with ischemic heart disease. 3 – 6 In the case of patients without ischemic heart disease, one trial . . .